INTEGRASI CSR DAN PROGRAM PERENCANAAN PEMBANGUNAN DAERAH DALAM KERANGKA MEWUJUDKAN MODEL BARU PELAKSANAAN CSR - Hakim, M. Lukman (Sawala : Jurnal Administrasi Negara, 2013)
Implementation of the concept of corporate social responsibility (CSR) is mainly not coincided with the local government policy.The local government development planner (Bappeda) designs its policy according to national plan and budget from the central government, whereas the company?s CSR team is doing ?business as usual? regardless whether its program?s design match with the government plan or not. Consequently, many of CSR projects do not reach satisfactory outcome as it clashed with governments? projects. A number of programs such as poverty alleviation, greening, and strengthening local economies that the company does are often collide with those from government. If there is a match, it leads to a double budgeting of same target place or a double counting in a program budget. This situation adds to the long list of classic local planning issues which is overlapping programs among government agencies. Hence, the implementation of CSR and the design of regional planning that are intended to further advance the regional development has often resulted in disappointment. An obvious example of this argument is in the case of PT Kalimantan Prima Coal (KPC) which operates in Kabupaten of Kutai Timur. Despite the fact that the district has a regional budget of Rp. 2.4 trillion, which is 86% of it obtained from the mine and mostly came from the royalty ofKPC, but the development process of the region is considered relatively slow. Many consider local government has failed in carrying out the development goal, whereas KPC is considered only want to make profits and ignoring the well-being of surrounding community.This paper argues that in order to find solution of this impasse formulation and a new conception is needed to integrate the company's CSR program with the development plan set out by the local government. By doing so, a new model of CSR is expected to be successfully implemented.